THE USE OF CLASSROOM LANGUAGES FOR BEGINNING LESSON IN MICRO TEACHING CLASS - Arianti, Arin (University of Surakarta, 2020)
The ability for beginning the lesson can encourage students’ interest and motivation earlier in learning. That view must be understood more by the students when they practiced in micro teaching subject. They were expected to apply it for training them in minimizes the use of mother tongue and maximize the use of target language. The aim of this research is to knowthe variation of classroom languages especially for beginning the lesson applied by sixth semester students in micro teaching practice. The method used in this research is descriptive qualitative. Data was collected by using observation and interview. The result shows that variation of classroom languages for beginning the lesson are still minimize and tend to be limited on certain terms. The most dominant type of classroom language used by students is greeting on using the term of “How are you”, the second one is the type of classroom language is register on using the term “who is absent today”. The last one is the type of timeto begin on using the term “let’s start our lesson now.” The students never applied the other terms in their practice.